Well-being at work in the Portuguese financial sector: the good, the bad and the others. A cross-sectional case-control study - Neto, Mariana (2017)
The aim of this study was to investigate the differences observed among employees with high scores (cases) and low scores (non-cases) on mental health related with workplace bullying, burnout, social support, sense of coherence and presenteeism. A cross-sectional study was carried out on a representative sample of 1114 employees of a national financial enterprise with CAWI data collection mode. An anonymous web questionnaire was applied to evaluate the effects of socio-demographic characteristics, workplace bullying, burnout, social support, sense of coherence and presenteeism on well-being at work. The well-being scale cut-off was used to compare the groups with and without well-being. Using a case-control methodology, chi-square tests were performed in order to estimate bivariate odds-ratios and logistic regression models were used to estimate multivariate odds-ratios. About 32% (n=353) of the employees completed the survey. Negative well-being overall prevalence was 40,7% (n=144) and was strongly associated with high emotional exhaustion (MBI), low scores of sense of coherence dimension manageability and overall social support. High levels of presenteeism completed work dimension were also associated with high levels of well-being. There was no association with workplace bullying even though it had a high prevalence (54%). Those associations were independent from socio-demographic characteristics. Emotional exhaustion seems to be the most important factor associated with well-being loss since sense of coherence manageability appears to have a protective effect. Workplace bullying needs further investigation to clarify its role on well-being loss because other relations can be present but not be captured by the methodological approach used. Employers and occupational physicians should be aware of the possible effects of burnout on well-being loss, of the effect of well-being loss on productivity decrease due to presenteeism and also of the sense of coherence protective effects in order to develop appropriate preventive measures.